The Chemical and Pharmaceutical Industry in China Opportunities and Threats for Foreign Companies - Festel, G.; Kreimeyer, A.; Oels, U.; von Zedtwitz, Maximilian (Springer Berlin Heidelberg : Imprint: Springer, 2005)
"Don't miss out on China!" and "What are you doing about China?" Catch phrases like these are spreading among managers all over the world. Just take a brief look at the business class occupancy of flights from Europe, North America or Japan to major Chinese cities: This gives you a glimpse of how business people are attracted by steady growth rates of 6 percent to 10 percent. It also indicates how much attention is given to a market featuring 1.3 billion potential consumers and a government committed to rapidly changing the country from an agricultu- dominated developing country into one of the world's economic powerhouses. Most of the global industrial players have had economic ties with China for decades already, but they were further strengthened after the country's opening to the world in the early 1980s. Furthermore, China's accession to the World Trade Or- nization is expected to catapult this already surging economy into another sphere of development.